Determinación de un modelo para el consumo de energía con suspensión total de sólidos en fluidos newtonianos - Ulate Brenes, Adolfo (Universidad de Costa Rica, 2011)
The development of a model for the power consumption in a mixing process for the suspension solids in a Newtonian liquid is proposed in this study. As a first step of this research, the critical variables were determined using an alternative method: the kind and size of the impellers (propeller and turbine, Da/Dt 0,333 and 0,433), the kind, size and quantity of solid (sand, volcanic stone and silica, 1,68x10-3 m and 7,07x10‑4 m in diameters); and the fluid. Two equations were developed to fix the experimental data, both using the same dimensionless numbers (One for Reynolds numbers lower than 60 000 and the other for Reynolds numbers between 60 000 and 150 000). These equations have similarities with the reported in the literature.